Eating habits and diet composition of Fringescale Sardinella (Sardinella fimbriata) found in Malampaya Sound, Palawan, Philippines - Vicente, Jesusito A. (2025)
Food determines an organism’s growth, development, movement, and survival. Its availability impacts fish interaction and density. A total of 607 individuals were collected between April 2023 and January 2024, with sizes ranging from total length of 11.0 to 15.8 cm to determine the food and feeding habits of fringescale sardinella. The fullness index was moderate to high (0.51-1.33), indicating an optimal and balanced feeding pattern. The study identified 34 food items from Phylum Annelida, Arthropoda, Chaetognatha, Chordata, Mollusca, and Ochrophyta. The prey consists of planktonic zooplankton, primarily copepods and mollusks, with percentage frequencies of occurrence of 84.6% and 57.6%, respectively. These values translate to very high indices of relative importance of 5,467 and 1,110. The presence of benthic-dwelling plankton was also noted, including amphipods, annelids, isopods, and ostracods. Some specimens contained diatoms (Coscinodiscus sp.). The computed diversity index (0.92) is low, but the evenness is close to 1. The Levin index was calculated at 3.60, implying that fringescale sardinella are generalists. Prey preference and abundance are affected by seasons. Males feed more intensely than females despite having higher energy requirements for reproductive needs.  Immature fish are more selective and consume smaller amounts of food, primarily small prey, while mature individuals use high-intensity feeding. As size increases, the prey preference becomes more specific. The p-value from the permutational multivariate analysis of variance (PERMANOVA), ranging from 0.0001 to 0.1394, indicates a significant difference in diet on season, maturity, and size.